The Influence of Financial Literacy on Green Investment Decisions - Theodorus Sutadi; Tri Rahmawati, Christina Heti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of financial literacy on green investment decisions. The research sample for part of the Z generation in Yogyakarta was 100 respondents. The data analysis technique used was purposive sampling. The data analysis technique uses simple linear regression analysis. The research results show that financial literacy influences green investment decisions. The implications of the results of this research are that the higher the financial literacy, the higher the green investment decisions so that people's welfare increases.